AN ANALYSIS FOR UNIT ROOT TESTING OF EMERGING ASIAN EQUITY MARKETS - Dr. Arpit Sidhu, CS Dr. Rupinder Katoch, Shubham kakran (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The present research article examined the descriptive statistics and unit-root among Asian equity markets. Present study has used daily closing price for 09 stock indices from Asian region over the period from 03 January 2003 to 31 August 2018. As the test of summary statistics and unit root are more sensitive towards the duration of the crisis period, underlying study has taken as the period of GFC (Global Financial Crisis) from 1 August 2007 to 31 March 2009; for ESDC (European sovereign debt crisis) from 02 May 2010 to 09 June 2013 and the rest of the period is considered as the post crisis period until the end date of the data collection. Present investigation helps to realize the detailed features and stationarity in the sample time-series data. The conclusive results of descriptive statistics and unit root are concerned, the lowest returns are to be found in Taiwan stock exchange but highest returns are found in various markets, say, Pakistan, Indonesia and Malaysia. Secondly, the highest volatility is found mostly in Chinese, Indian and Pakistanis stock exchanges. The lowest volatility found in Malaysian stock exchanges in all sample periods and structural breaks.So far stationarity is concerned, all the sample time periods show stationarity at first difference. Present study also establish relevant information for investors, policymakers, researchers and hedgers for future and further analysis with emerging financial modelling.